Efficiency of Student-made Illustrative Materials in Early School Age - Phutkaradze, Nana; Chkhaidze, Nanuli (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The use of visual aids in the teaching and learning process plays a crucial role in students‘ perception, understanding, and comprehension. For younger students in particular, visual materials are one the most effective ways to increase interest and motivation for learning. practice shows that verbal explanations alone are less effective – information supported by visual aids perceived more deeply and retained longer in memory. within the framework of our research, special attention was given to the process of creating visual aids, in which students themselves are actively involved. they are given opportunity to search for end collect resources Independently, select information within their capabilities, and then create visual materials during the lesson. this approach engages the entire class, fostering both motivation and e sense of the study clearly demonstrated that in the groups where students created the visual aids themselves, academic achievement levels were significantly higher than in those groups where the materials were prepared solely by the teacher . This indicates that active student participation in the learning process not only improves comprehension and retention but also promotes the development of critical and creative thinking skills.